2009
DOI: 10.1136/qshc.2009.032771
|View full text |Cite
|
Sign up to set email alerts
|

Improving healthcare worker hand hygiene adherence before patient contact: a before-and-after five-unit multimodal intervention in Tuscany

Abstract: Although overall healthcare worker adherence with hand hygiene procedures before patient contact substantially increased after the multimodal intervention, considerable variability-for both nurses and doctors and across the 5 units-was seen. Although adherence substantially increased, overall hand hygiene in these units could still be greatly improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
0
28
0
4
Order By: Relevance
“…In fact, it has been shown that many reasons for non compliance are given, but vigilant in-house infection control teams can facilitate compliance [11,32].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that many reasons for non compliance are given, but vigilant in-house infection control teams can facilitate compliance [11,32].…”
Section: Discussionmentioning
confidence: 99%
“…19 Appropriate hand hygiene was defined as the use of soap and water or alcohol-based hand rub before patient contact, which corresponds to the first moment of the WHO's 5 moments of hand hygiene. 11 Hand hygiene practice prior to patient contact for each individual provider-patient encounter was observed and recorded using the hand hygiene observation form adapted from a previous study by Saint et al 6,20 Identical to the preintervention study, 19 the form captured the following information: unit in which observations were performed, time of initiation and completion of observations, healthcare worker subgroup (physician or nurse), and the type of hand hygiene before patient contact (ie, hand washing with soap and water, use of alcohol-based hand rub, or no hand hygiene). Unit physicians and nurses were informed that their clinical practices were going to be observed, but were not informed of the purpose of the observations (eg, hand hygiene adherence).…”
Section: Observation Of Hand Hygiene Practicementioning
confidence: 99%
“…4 In Japan, nearly 9% of patients admitted to the intensive care unit (ICU) develop an infection during hospitalization, 5 and 5% of all patients hospitalized become infected with methicillinresistant Staphylococcus aureus. 6 The management of healthcare-associated infections in Japan accounts for up to 5% of total annual healthcare costs, with an estimated $6.8 billion estimated to be potentially preventable. 7 In addition, healthcare-associated infections are associated with increased length of stay in the hospital.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, studies such as the one by Saint and colleagues3 seek to demonstrate both that hand hygiene can be improved and how it can be improved (see page ) . This is information we sorely need.…”
mentioning
confidence: 99%